Development And Evaluation Of Terbutaline Sulphate Loaded-Biodegradable Microspheres For Pulmonary Delivery [RM301.42. A286 2007 f rb]. - Mohammed Ahmed, Rehab Abdallah (2007)
Mikrosfera terbutalin sulfat (TBS) pelepasan tertahan dibangun menggunakan polimer PLA R 203H dan PLGA RG 504H.